2005
DOI: 10.1583/04-1496.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Aortoureteric Fistula

Abstract: ࡗ ࡗPurpose: To report successful endovascular treatment of massive hemorrhage from an aortoureteric fistula. Case Report: An 82-year-old man who had undergone total cystectomy and bilateral ureterostomy for bladder cancer was transferred with massive hemorrhage from the ureterostomy. Angiography demonstrated an aortoureteric fistula between the terminal aorta and the left ureter. The patient had pancytopenia from unknown causes on admission, so a stent-graft made from a Gianturco Z-stent covered with Dacron gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Besides, the fistula has to be demonstrated radiographically, which is not always possible if there is no active bleeding at that moment. 1,5 Hence, this kind of fistula is difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the fistula has to be demonstrated radiographically, which is not always possible if there is no active bleeding at that moment. 1,5 Hence, this kind of fistula is difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…The causative factor has been attributed to prolonged stent placement. [2][3][4][5][6] Most cases report prolonged duration of stent placement varying from 5 months to 15 years before the onset of hematuria. 3,4 The hematuria is either intermittent or life-threatening, with some patients presenting spontaneously and others during stent exchange.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Most complications are common in the setting of previous vascular surgery and/or atherosclerosis. Establishing a diagnosis in complex cases is often difficult; in the presence of hematuria a high index of clinical suspicion is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Asham et al 7 reported the fi rst successful case of ureteroarterial fi stula treated by a stent graft. Ota et al 5 reported the successful endovascular treatment of an aortoureteric fi stula, with the stent graft being free from infection on the 42nd day after surgery, as revealed at autopsy following death from leukemia.…”
Section: Discussionmentioning
confidence: 99%